2010
DOI: 10.1179/147842210x12710800383567
|View full text |Cite
|
Sign up to set email alerts
|

Intentional patina of metal archaeological artefacts: non-destructive investigation of Egyptian and Roman museum treasures

Abstract: This paper describes microstructural analyses by X-ray portable diffraction and microdiffraction on intentional patina of the bronze museum objects from antique Egypt and the Roman Empire. They bring evidence of the presence in the true black bronze patinas of metallic gold and/or silver presumably as nanoparticles. Three other Egyptian patinas not belonging to black bronze are characterised. Apparent black patination on a Roman scalpel handle is discussed. The discovery of a new patination procedure on Roman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In ancient Greece, as an example, recipes for the realisation of brown and black patinas were quite diffusely employed, even if, at that time, a bright and polished surface resembling gold was generally preferred [2,47]. Moreover, the production of black patinas has been reported on Egyptian and Roman artefacts [48,49]. During the Italian Renaissance, then, the realisation of brown and reddish patinas was largely diffused [44,47,48].…”
Section: Artistic Patinamentioning
confidence: 99%
“…In ancient Greece, as an example, recipes for the realisation of brown and black patinas were quite diffusely employed, even if, at that time, a bright and polished surface resembling gold was generally preferred [2,47]. Moreover, the production of black patinas has been reported on Egyptian and Roman artefacts [48,49]. During the Italian Renaissance, then, the realisation of brown and reddish patinas was largely diffused [44,47,48].…”
Section: Artistic Patinamentioning
confidence: 99%
“…These treatments, giving a black or velvet colour to the surface of the artefact, were applied on specific copper alloys containing gold (1-8 wt%) and silver (1-4 wt%). Combined to micro-scale investigations (micro-Raman spectroscopy, SEM, ICP-AES…) in a tailored step by step analytical strategy, a comprehensive study performed these last years on several pieces from the Louvre Museum (Aucouturier et al 2010), used an Ion Beam Analysis approach by Rutherford Back Scattering (RBS) to decipher the nature of the layer with a resolution of about 100 nm. It was demonstrated that small amounts of Au and Ag inside Cu 2 O layer allowed to change the colour and to obtain the desired one.…”
Section: Artificial Patinas and Ancient Surface Treatments On Bronzesmentioning
confidence: 99%
“…The most prominent examples having artificial surface layers are the Bronze Age daggers and vessels from the Mycenaean shaft graves and other Greek locations. In addition, a large corpus of Egyptian and Roman artefacts with metal inlays has been identified as intentionally patinated in the last decades (Craddock, 1982;Giumlía-Mair and Craddock, 1993;Giumlía-Mair, 1996a;1996b;Giumlía-Mair and Riederer, 1998;Mathis et al 2007Mathis et al , 2009Aucouturier et al 2010;Giumlía-Mair, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…They have initially been investigated by Mathis (2005, Fig. 72, 163e164), but later on Aucouturier et al (2010) confirmed them to be treated thermally deliberately at around 600 C. In contrast to the Egyptian items, one of the two Roman objects has copper inlays in a bronze base. This appears fairly unusual because during prolonged heating at temperatures of 500 C or above the alloying elements from the metal base (especially tin) might migrate into the copper inlays and potentially cause the formation of irregular and undesired seams.…”
Section: Introductionmentioning
confidence: 98%